Characterization of multiple SPS knockout mutants reveals redundant functions of the four Arabidopsis sucrose phosphate synthase isoforms in plant viability, and strongly indicates that enhanced respiration and accelerated starch turnover can alleviate the blockage of sucrose biosynthesis. (September 2015) - Bahaji, Abdellatif; Baroja-Fernández, Edurne; Ricarte-Bermejo, Adriana; Sánchez-López, Ángela María; Muñoz, Francisco José; Romero, Jose M.; Ruiz, María Teresa; Baslam, Marouane; Almagro, Goizeder; Sesma, María Teresa; Pozueta-Romero, Javier
Highlights: We produced and characterized multiple SPS knock-out mutants of Arabidopsis. The four SPS isoforms overlap in plant growth and nonstructural carbohydrate metabolism. SPS is essential for plant viability. Enhanced respiration and starch turnover alleviate blockage of sucrose biosynthesis. Sucrose is mainly synthesized through the SPS-SPP pathway in Arabidopsis. Abstract: We characterized multiple knock-out mutants of the four Arabidopsis sucrose phosphate synthase (SPSA1, SPSA2, SPSB and SPSC) isoforms. Despite their reduced SPS activity, spsa1/spsa2, spsa1/spsb, spsa2/spsb, spsa2/spsc, spsb/spsc, spsa1/spsa2/spsb and spsa2/spsb/spsc mutants displayed wild type (WT) vegetative and reproductive morphology, and showed WT photosynthetic capacity and respiration. In contrast, growth of rosettes, flowers and siliques of the spsa1/spsc and spsa1/spsa2/spsc mutants was reduced compared with WT plants. Furthermore, these plants displayed a high dark respiration phenotype. spsa1/spsb/spsc and spsa1/spsa2/spsb/spsc seeds poorly germinated and produced aberrant and sterile plants. Leaves of all viable sps mutants, except spsa1/spsc and spsa1/spsa2/spsc, accumulated WT levels of nonstructural carbohydrates. spsa1/spsc leaves possessed high levels of metabolic intermediates and activities of enzymes of the glycolytic and tricarboxylic acid cycle pathways, and accumulated high levels of metabolic intermediates of the nocturnal starch-to-sucrose conversion process, even under continuous light conditions. Results presented in this work show that SPS is essential for plant viability, reveal redundant functions of the four SPS isoforms in processes that are important for plant growth and nonstructural carbohydrate metabolism, and strongly indicate that accelerated starch turnover and enhanced respiration can alleviate the blockage of sucrose biosynthesis in spsa1/spsc leaves.